2020
DOI: 10.1071/bt19170
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of silver nanoparticles on the germination and root development of lettuce (Lactuca sativa)

Abstract: The advancement of nanotechnology has increased use of nanoparticles in industrial scale. Among the most used nanoparticles are those silver-based. Large-scale use can raise levels of these nanoparticles in aquatic environments, which, in turn, presents potential risks to aquatic organisms and ecosystems, causing undesired environmental impacts. To evaluate the potential risk of the silver nanoparticles (AgNPs) interaction with plants, seeds of Lactuca sativa L. (Asteraceae) were exposed to different concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The supernatant was saved in separate falcon tubes and kept at 4 °C for high performance liquid chromatography (HPLC, Bahawalpur, Pakistan). Note: Various concentrations of the AgNO3 aqueous solution (0.5, 1, and 2 mM) and plant extract (10,20, and 40 mL) were used to determine their impact on the growth of Ag NPs. The morphology and size were determined using transmission electron microscope (TEM) images by JEOL JEM 2100.…”
Section: Biosynthesis Of Silver Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The supernatant was saved in separate falcon tubes and kept at 4 °C for high performance liquid chromatography (HPLC, Bahawalpur, Pakistan). Note: Various concentrations of the AgNO3 aqueous solution (0.5, 1, and 2 mM) and plant extract (10,20, and 40 mL) were used to determine their impact on the growth of Ag NPs. The morphology and size were determined using transmission electron microscope (TEM) images by JEOL JEM 2100.…”
Section: Biosynthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…Moreover, there are studies which offer evidence that NPs contribute more to their toxicity than the Ag + dissociation [17,18]. To date, many efforts have been put forward to explore the impact of metallic NPs on plant growth and life, especially metals such as silver, since the production of Ag NPs will reach 1216 tons by 2020 and 614.4 mg/kg will be deposited in the sediments [19,20]. With their impact on the biological system at a molecular level not fully understood, it is important to strengthen the knowledge at a molecular level and explore the mechanisms that mediate the effect of Ag NPs in plants.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the water treatment as control had no significant effect on dry weight, and the three variations in colloidal AgNPs showed a mean significance value that was not much different (Figure 4). Pinheiro et al [3] examined the germination parameters of lettuce seeds exposed to AgNPs (15 nm in size) at various concentrations for 7 days. The results showed that lettuce exposed with 12.5, 25, and 50 mg/L AgNPs also showed no significant difference between treatments.…”
Section: Resultsmentioning
confidence: 99%
“…They are used in coatings for surgical gowns, face masks, and dressings for post-surgical wound healing. As a biosensor material, AgNPs can be used to detect penicillin on food packaging and agricultural products such as fertilizer application systems [1][2][3]. According to Mueller & Nowack (2008) [4], the global production of AgNPs can reach 500 tons per year (t/a).…”
Section: Introductionmentioning
confidence: 99%
“…Due to high hydrophobicity and large surface area of MPs, they have become carrier for pathogens and many other pollutants [15,16]. Additionally, they have been ingested by many organisms through food chain, which results in negative effects on ecosystem and human health [1,17,18]. Therefore, the pollution caused by MPs and their eco-toxicological effects need more researches in future.…”
Section: Introductionmentioning
confidence: 99%